Defining complexity in anaesthesia: description and validation of the Oxford Anaesthetic Complexity (OxAnCo) score. (16th August 2022) - Ridgeon, E.; Wilson, K.; Wilkinson, D.; Douglass, P.; Elrefaey, A.
Summary: Increasing demand for surgery and anaesthesia has created an imperative to manage anaesthetic workforce and caseload. This may include changes to distribution of cases amongst anaesthetists of different grades, including non‐physician anaesthetists. To achieve this safely, an assessment of case complexity is essential. We present a novel system for scoring complexity of cases in anaesthesia, the Oxford Anaesthetic Complexity score. This integrates patient, anaesthetic, surgical and systems factors, and is different from assessments of risk. We adopted an end‐user development approach to the design of the score, and validated it using a dataset of anaesthetic cases. Across 688 cases, the median (IQR [range]) complexity score was 19 (17–22 [15–33]). Cases requiring a consultant anaesthetist had a significantly higher median (IQR [range]) score than those requiring a senior trainee at 22 (20–25 [15–33]) vs. 19(17–21 [15–28]), p < 0.001. Cases undertaken in a tertiary acute hospital had a significantly higher score than those in a district general hospital, the median (IQR [range]) scores being 20 (17–22 [15–33]) vs. 17 (16–19 [17–28]), p < 0.001. Receiver‐operating characteristic analysis showed good prediction of complexity sufficient to require a consultant anaesthetist, with area under the curve of 0.84. Any rise in complexity above baseline (score > 15) was strongly predictive of a case too complex for a junior trainee (positive predictive value 0.93). The Oxford Anaesthetic Complexity score can be used to match cases to different grades of anaesthetist, and can help in defining cases appropriate for the expanding non‐physician anaesthetist workforce.